Eating psychopathology as a risk factor for depressive symptoms in a sample of British athletes - Shanmugam, V.; Jowett, S.; Meyer, C. (Journal of Sports Sciences, 2014)
Within the clinical literature it is accepted that there is a strong connection between eating disorders and depression; however the nature of the casual relationship is somewhat unclear. Therefore the aim of the present study was to determine the prospective relationship between eating psychopathology and depressive symptoms among competitive British athletes. A total of 122 athletes completed the Eating Disorder Examination Questionnaire and the depression subscale of the Symptom Checklist-90R over a 6-month period. Partial correlations revealed that when controlling for baseline eating psychopathology, athletes` baseline depressive symptoms was not related to their eating psychopathology 6 months later. However, when controlling for baseline depressive symptoms, athletes` initial eating psychopathology was positively and significantly related to depressive symptoms 6 months later. Subsequent hierarchical multiple regression analyses revealed athletes` initial levels of eating psychopathology significantly predicted depressive symptoms 6 months later. The current findings support the assertion that elevated eating psychopathology serves as a potential risk factor for the development of depression in athletes. Thus, National Governing Bodies, athletic clubs, sport organisations and universities need to recognise and be aware that exposure to the factors that increase the risk of eating disorders inadvertently serves to increase athletes` vulnerability for depression.